(untitled) (Contemporary Mathematics, 2023)
This comprehensive review concerns the trilogy about Sylow Theory in Locally Finite Groups which has been published in four books by Books on Demand (BoD), Norderstedt, Germany, namely: Part 1 - ISBN 978-3-7543-6087-3 (November 2022); Part 1 - Second edition - ISBN 978-3-7568-0801-4 (March 2023); Part 2 - ISBN 978-3-7568-3892-9 (December 2022); Part 3 - ISBN 978-3-7568-9853-4 (January 2023).